2001
DOI: 10.1103/physrevb.64.233102
|View full text |Cite
|
Sign up to set email alerts
|

Direct spectroscopy of a deep two-dimensional photonic crystal microresonator

Abstract: Photonic crystals based on macroporous silicon with fundamental band gaps in the middle infrared region 3.4-5.8 m were fabricated. Scanning probe optical microscopy and laser spectroscopy were combined to examine a deep two-dimensional photonic crystal microresonator based on a single point defect. Two sharp resonances were recorded in the band gap, in excellent agreement with the results of numerical simulations. Such a microresonator with high-quality factors and a subwavelength mode extension could be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…On the other hand, four air holes, i.e., a sort of point defects, have been introduced at the center of said silicon waveguide of PhCWG to form a resonator structure. It is reported that two of high-resonances centered at wavelengths 3.621 and 3.843 m. The quality factors of these two resonant wavelength peaks were measured as 640 and 190, respectively [20]. Sandoghdar et al have applied scanning near-field optical microscopy (SNOM) to visualize the optical intensity topography around these four air holes of this microresonator structure.…”
Section: Configuration and Modeling Of Phcwg Microresonator Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, four air holes, i.e., a sort of point defects, have been introduced at the center of said silicon waveguide of PhCWG to form a resonator structure. It is reported that two of high-resonances centered at wavelengths 3.621 and 3.843 m. The quality factors of these two resonant wavelength peaks were measured as 640 and 190, respectively [20]. Sandoghdar et al have applied scanning near-field optical microscopy (SNOM) to visualize the optical intensity topography around these four air holes of this microresonator structure.…”
Section: Configuration and Modeling Of Phcwg Microresonator Devicesmentioning
confidence: 99%
“…We conduct the simulation throughout the whole study upon this assumption. In contrast to the case of the layout dimensions used in [20] and [21], i.e., designing for resonant wavelengths in far infrared region, we optimize our PhCWG designs to enable the output resonant wavelength peaks appeared in the wavelength range of 1550 to 1620 nm, i.e., the near-infrared region. The common optical spectrum analyzer (OSA) used in optical communication industry can give us down to a 0.1-nm resolution of measuring resonant wavelength within this region.…”
Section: Configuration and Modeling Of Phcwg Microresonator Devicesmentioning
confidence: 99%
“…When the coupling conditions are satisfied, the resonant mode confined near the sensor surface is excited, and exhibits amplified field intensity, which enhances the fluorescent dye emission immobilized within a 200 nm region above the PC surface [25]. Unlike evanescent coupled optical micro-or nano-resonators [26,27], which require highly precise position control, input light is coupled into PC resonator mode via angle and wavelength control. When most of the excitation beam is coupled into resonant mode, the near field strength becomes strong and consequently the PC sensor provides fluorescence enhancement.…”
Section: Chapter 2: Coupling Of Pc Sensor and Excitation Lightmentioning
confidence: 99%
“…These systems have been the subject of considerable interest during the past several years because they have the potential to be used to develop a new technology completely based on optical integrated circuits [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Today, research in photonic crystals (PC) indicates that suitable technological applications require the design and application of photonic heterostructures rather than simple systems [16][17][18].…”
Section: Introductionmentioning
confidence: 99%